2019
DOI: 10.1101/713511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural fuzziness of the RNA-organizing protein SERF1a determines a toxic gain-of-interaction

Abstract: Members of the MOAG/SERF protein family have been attributed a neuropathologic significance because of their ability to enhance the proteotoxic polymerization of amyloidogenic proteins such as alpha-Synuclein (aSyn). However, the cellular function remains unknown. Here, we identify SERF1a as an RNA-organizing protein i) with no structural homology to canonical RNA-binding proteins, ii) with an RNA-chaperoning activity which favours the incorporation of RNA into nucleoli and liquid-like artificial RNAorganelles… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, under stress conditions, it was shown to migrate to the cytoplasm, where it could drive amyloid toxicity. 88 While there was no compensatory upregulation of SERF1 in response to SERF2 KO and a similar mode of action remains to be demonstrated for SERF2, the structural (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, under stress conditions, it was shown to migrate to the cytoplasm, where it could drive amyloid toxicity. 88 While there was no compensatory upregulation of SERF1 in response to SERF2 KO and a similar mode of action remains to be demonstrated for SERF2, the structural (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 96%
“…The copyright holder for this preprint this version posted January 5, 2021. ; https://doi.org/10.1101/2021.01.05.423442 doi: bioRxiv preprint SERF1A through a region which is highly conserved in MOAG-4 and SERF2 86 . In this study, we have demonstrated in cells and mice that SERF2 provides a growth advantage during development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrostatic interactions between MOAG-4/SERF1a and alpha-synuclein accelerate the formation of alpha-synuclein fibrils ( Falsone et al, 2012 ; Yoshimura et al, 2017 ; Merle et al, 2019 ). This aggregation-promoting effect of SERF on alpha-synuclein was recently suggested to be a toxic side effect, mediated by an interaction between SERF1a and the negatively charged C-terminus of alpha-synuclein ( Meyer et al, 2019 ). This study suggested that SERF1a acts as an RNA chaperone in the formation of liquid-like RNA organelles.…”
Section: Protein Homeostasis Declines With Agingmentioning
confidence: 99%
“…This study suggested that SERF1a acts as an RNA chaperone in the formation of liquid-like RNA organelles. Under stressful conditions, RNA and alpha-synuclein may compete for SERF binding, possibly favoring an interaction between alpha-synuclein and SERF that accelerates amyloid formation ( Meyer et al, 2019 ). Such stressful conditions could arise during aging as protein homeostasis declines.…”
Section: Protein Homeostasis Declines With Agingmentioning
confidence: 99%